SURVEI OF MAMALIA IN MAMBERAMO-FOYA AREA - Aksamina Yohanita; Kris Helgen; Yance de Fretes (Jurnal Natural, 2007)
A Rapid Assessment Program survey (RAP survey) was carried out at Kwerba and the Foya mountains, Papua on November-December 2005. The survey was intended to search for the diversity of mammalian species in the area of Kwerba village, Mamberamo River, Muara Manirim and Muara Hotije (on the lowland) and the Foya mountains (on the highland). The survey found 38 species of mammalian, grouped into 13 family. One spectacular founding was the recording of two unique species, the “kanguru pohon mantel emas” (Dendrolagus pulcherrimus) and the “landak Irian” (Zaglossus sp.).